Measure The Significance of Learning Value and Trust Factors for Online Learning Technology Acceptance in Indonesia - Yuda Dian Harja; Mohammad Isa Irawan; Rita Ambarwati (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
One of the main stages to achieve the success of online learning technology is the acceptance of the technology by its users. Therefore, identifying how significant the influence of a factor in the success of technology acceptance is very important. This study aims to measure the significance of learning value and trust factors on the acceptance model of online learning technology. To test the research hypothesis used the Partial Least Square Structural Equation Modeling (PLS-SEM) method. This research is a quantitative study with a survey approach to respondents, where respondents must have used online learning technology. The result of the study shows the influence of learning value and trust factors on the acceptance of online learning technology is significant. The results of the study can be taken into consideration for providers of online learning technology in Indonesia as a reference in making strategic decisions for further development.